Invented spelling and perspectives on spelling development : the necessity of an integrated cognitive model - Silva, Ana (2019)
There are several models about the mechanism that make pre-school children evolve regarding the quality of their invented spelling. Ehri's teorical perspective (1997) describes the development of children's spelling skills in terms of their increasing ability to map sounds of words to phonetically appropriate letters. According to this perspective, written language is conceived as an instrument for translating oral language and phonological awareness determines the precision of invented spelling. This model neglects linguistic variables that might influence children ability to analyse the oral and written language and also does not conceive children's reflection about written code as a factor of evolution. The constructivist perspective from Ferreiro (1988), emphasizes the importance of internal conflict between different criterion about the organization of the alphabetic code. For instance, the repetition of the same vowel in syllabic phonetised writing might cause a conflict in children's thinking with another criterion that they attaint, related with the variation of letters within the written word (e.g. Nunes Carraher and Rego (1984) cited a Portuguese-speaking child who spelled urubu 'vulture' as UUU). This conflict might lead children to analyse syllables in their phonemes and became a source for an alphabetic approach of writing. This and other conflicts are the main factor, from the point of view of this theory, for the evolution of children's conceptions about written language. However those mechanisms are described independently of children ability to analyse oral words or the frequency of words and the articulatory properties of phonemes that integrate those words. On the other hand, Polo, Kessler and Treiman (2005), think that that statistical learning skills exists from an early age. These skills are applied in learning to spell, as in other tasks. This perspective emphasizes that children's writing reflects the characteristics of the input to which they have been exposed as they try to find meaningful patterns in regularities of written language. These regularities give children information about graphical as well as phonological patterns of the language in which they reflected their very early spellings. However, this perspective never analyses the nature of children thinking and how that reflects their approach to written language. It is quite important to create a model that integrates these several contribution. © 2011 by Nova Science Publishers, Inc. All rights reserved.